Robust Biocompatible Fibers from Silk Fibroin Coated MXene Sheets. Issue 9 (23rd February 2023) - Usman, Ken Aldren S.; Yao, Ya; Bacal, Christine Jurene O.; Zhang, Jizhen; Jarvis, Karyn L.; Lynch, Peter A.; Mota‐Santiago, Pablo; Qin, Si; Naebe, Minoo; Henderson, Luke C.; Hegh, Dylan Y.; Allardyce, Benjamin J.; et al.
Abstract: Conductive fibers are needed for the development of flexible electronic and biomedical devices. MXene fibers show great promise for use in such applications because of their high conductivity. Current literature on MXene fiber development highlights the need for improving their mechanical properties and investigation of biocompatibility. Here the use of silk fibroin biopolymer as a MXene formulation additive for the production of MXene fibers is studied. It is found that the favorable silk fibroin–MXene interactions resulted in improved durability, withstanding up to 1 h of high frequency sonication in buffered solutions. Furthermore, fibers with ≈5 wt% silk fibroin displays interesting properties including high conductivity (≈3700 S cm −1 ), high volumetric capacitance (≈910 F cm −3 ), and non‐cytotoxicity toward THP‐1 monocytic cells. The results presented here provide an important insight into potential use of MXene fibers in flexible electronics and biomedical applications. Abstract : A new investigation of MXene–silk fibroin composite fibers is presented. The favorable interfacial interactions between silk and MXene resulted in outstanding mechanical and electrical properties. Their biocompatibility provides an important insight into their potential use in flexible electronics and biomedical applications.